Expansion of a Bose-Einstein condensate formed on a joint harmonic and one-dimensional optical-lattice potential - Adhikari, S. K. (Iop Publishing Ltd, 2003)
We study the expansion of a Bose-Einstein condensate trapped in a combined optical-lattice and axially-symmetric harmonic potential using the numerical solution of the mean-field Gross-Pitaevskii equation. First, we consider the expansion of such a condensate under the action of the optical-lattice potential alone. In this case the result of numerical simulation for the axial and radial sizes during expansion is in agreement with two experiments by Morsch et al (2002 Phys. Rev. A 66 021601(R) and 2003 Laser Phys. 13 594). Finally, we consider the expansion under the action of the harmonic potential alone. In this case the oscillation, and the disappearance and revival of the resultant interference pattern is in agreement with the experiment by Muller et al (2003 J. Opt. B: Quantum Semiclass. Opt. 5 S38).